Effect of Heparin on TAFI-Dependent Inhibition of Fibrinolysis: Relative Importance of TAFIa Generated by Clot-Bound and Fluid Phase Thrombin - Colucci, Mario; Pentimone, Anna; Binetti, Bianca M.; Cramarossa, Marialisa; Piro, Donatella; Semeraro, Nicola (Thrombosis and Haemostasis, 2002)
Heparin has been proposed to enhance thrombolysis by inhibiting thrombin-dependent generation of activated TAFI (thrombin activatable fibrinolysis inhibitor), a carboxypeptidase that inhibits fibrinolysis. We evaluated the effect of heparin in an in vitro thrombolysis model consisting of a radiolabelled blood clot submerged in defibrinated plasma. Fibrinolysis was induced by adding t-PA (250 ng/ml) and calcium to the plasma bath. Control experiments indicated that thrombin generation induced by recalcification caused significant TAFI activation and inhibited clot lysis. Heparin (up to 1 U/ml), added to the plasma bath, failed to enhance clot lysis. Thrombin generation in the fluid phase was totally inhibited by heparin at concentrations > 0.5 U/ml. In contrast, thrombin generation on the clot surface was not inhibited by heparin (1 U/ml). TAFIa generation did occur in heparin-containing samples (1 U/ml) and amounted to about 10% of TAFIa formed in control samples. This low amount of TAFIa did exert antifibrinolytic activity as indicated by the observation that the addition of a specific TAFIa inhibitor (PTI) along with heparin enhanced clot lysis. Hirudin (10 µg/ml), at variance with heparin, inhibited clot-bound thrombin and enhanced clot lysis. These data show that heparin is unable to stimulate fibrinolysis through a TAFI-dependent mechanism, most likely because of its inefficiency in inhibiting thrombin generation on the clot surface. Moreover, they suggest that clot-bound thrombin plays a major role in TAFI-mediated inhibition of fibrinolysis through “localized” TAFIa generation.
Keywords: Thrombin; thrombin inhibitors; clot lysis; carboxypeptidase